Mangiferin Content in N-Hexane and Diethyl Ether Fractions of Mango (Mangifera indica L.) Leaves Var. Gedong Gincu : - Luviriani, Eva; Calyptranti, Rosellynia; Jehan, Nabilah Nauli (STMIK Widya Cipta Dharma, 2024)
Mango (Mangifera indica L.) is a tropical fruit plant with high economic value and potential as a source of phytopharmaceuticals. One notable mango variety is Gedong Gincu, originating from Majalengka Regency, West Java, which contains active compounds such as mangiferin, flavonoids, saponins, and tannins with various therapeutic effects. This study aims to compare the mangiferin content in the n-hexane and diethyl ether fractions of Gedong Gincu mango leaf extract using the Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) method. Mango leaves were extracted with ethanol, followed by fractionation using n-hexane and diethyl ether. The resulting fractions were then analyzed for mangiferin content using RP-HPLC. The weights of the n-hexane and diethyl ether fractions were 13.418 g and 8.21 g, respectively. Phytochemical screening revealed the presence of flavonoids, alkaloids, phenols, tannins, and saponins. RP-HPLC analysis showed differences in mangiferin content between the two fractions, with retention times (RT) of 1.430 minutes for the n-hexane fraction and 1.473 minutes for the diethyl ether fraction, indicating variations in solubility and interaction with the mobile phase. The RP-HPLC quantification revealed that the n-hexane fraction contained 339.5 mg/L of mangiferin, while the diethyl ether fraction contained 547.3 mg/L. This study provides valuable insights into the comparison of extraction solvents for mangiferin, which can be further utilized in the development of herbal formulations.